2010
DOI: 10.1021/jp9092089
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Hydrocarbon Sensitivity on the Distance of Linked Phenyl Group to CdSe Quantum Dots Surfaces

Abstract: The hydrocarbon sensing properties of CdSe semiconductor quantum dots (QDs) tailored with benzoic, phenylacetic, 4-phenylbutanoic, or 6-phenylhexanoic acids as a surface enhancement agent have been studied to determine their dependence on the phenyl group distance from the QD surface. QDs of roughly the same size were used to attach each of the mentioned surface agents with similar surface coverages, as determined by nuclear magnetic resonance technique, followed by drop-coating and drying of the QD solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Magnetic metal oxide nanocrystals, including iron-and manganese oxides, have shown considerable potential for application in radionuclide sorption, separation, sensing, and stabilization, all of which remain critical challenges for a number of disciplines. [1][2][3][4][5][6][7][8] For uranium in particular, such nanoscale oxide materials have demonstrated high sorption capacities due to both high surface to volume ratios, thermodynamically favorable surface chemistries (for chemisorption), and enhanced (surface) redox potentials. Varied oxidation states of surface transition metal ions (iron(II and III) and manganese(II, III, and IV)) underpin such processes including facile reduction and thus immobilization of soluble uranyl(VI) as uranium(IV) precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic metal oxide nanocrystals, including iron-and manganese oxides, have shown considerable potential for application in radionuclide sorption, separation, sensing, and stabilization, all of which remain critical challenges for a number of disciplines. [1][2][3][4][5][6][7][8] For uranium in particular, such nanoscale oxide materials have demonstrated high sorption capacities due to both high surface to volume ratios, thermodynamically favorable surface chemistries (for chemisorption), and enhanced (surface) redox potentials. Varied oxidation states of surface transition metal ions (iron(II and III) and manganese(II, III, and IV)) underpin such processes including facile reduction and thus immobilization of soluble uranyl(VI) as uranium(IV) precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…10,27,44 For example, it has been proposed to surface-modify CdSe core dots for sensitive and selective detection of aromatic hydrocarbon vapors by utilizing a combination of stabilizing ligands (TOPO and stearic acid (SA)) and interaction-enhancing functional agents. 10,28,38 As for the latter, the surface-modifying group such as benzoic acid (BA) is expected to enhance the QD interaction with the aromatic hydrocarbons through electrostatic π -π interactions between the grafted group and the target analyte.…”
Section: Quantum Dot Surface Modifi Cationmentioning
confidence: 99%
“…Thus, it is of interest to study the dependence of hydrocarbon sensitivity on the distance of the linked phenyl group to the QD surfaces. 28 CdSe QDs of roughly the same size were synthesized with in situ attachment of BA, phenylacetic (PA), 4-phenylbutanoic (PBA), or 6-phenylhexanoic acids (PHA) surface agents with similar surface coverage, as determined by nuclear magnetic resonance techniques. This is important to confi rm since, as noted above, different surface coverage will likely affect the degree of ligand to QD charge transfer effects.…”
Section: Surface-modifying Group Length Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…We incorporated CdSe nanocrystals of different diameters into a poly­(methyl methacrylate) (PMMA) film and have found that each size of CdSe nanocrystals in this polymeric nanocomposite unexpectedly demonstrated its own photoluminescence (PL) response pattern upon exposure to polar and nonpolar vapors in air. Single-size/single-color CdSe quantum dots with different surface modifying groups were also encapsulated into PMMA films and porous anodic aluminum oxide substrates , to study their response to organic vapors.…”
Section: Introductionmentioning
confidence: 99%